2006
DOI: 10.1177/097300520600200207
|View full text |Cite
|
Sign up to set email alerts
|

Personal and Economic Empowerment in Rural Indian Women

Abstract: The present study examined the empowerment of women by addressing two dimensions: economic empowerment and personal empowerment. One hundred women, aged between 16 and 65 years, participating in self-help groups from two rural Indian villages in North-West India took part in the study. Both quantitative and qualitative data were gathered through self-report surveys and interviews, with the analysis yielding contradictory findings. The quantitative data found that working women reported moderate to high levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 30 publications
4
54
0
Order By: Relevance
“…Aruna and Jyothirmayi [24] revealed that microfinance had significant influence on economic position. Moyle et al [26] found that women in income generating activities give support to economic empowerment. Though our study has not considered economic position as indicator of women empowerment but economic security also develops from better economic position.…”
Section: Paired Samples T Test Results For Economic Security (Es)mentioning
confidence: 99%
See 1 more Smart Citation
“…Aruna and Jyothirmayi [24] revealed that microfinance had significant influence on economic position. Moyle et al [26] found that women in income generating activities give support to economic empowerment. Though our study has not considered economic position as indicator of women empowerment but economic security also develops from better economic position.…”
Section: Paired Samples T Test Results For Economic Security (Es)mentioning
confidence: 99%
“…According to Moyle et al [26], women in income generating activities give support to personal and economic empowerment. Another study conducted by Nader [27] found that microcredit improved health and harmony in the family.…”
Section: Microfinance and Women Empowermentmentioning
confidence: 99%
“…Studies, such as Nair (2005), Moyle, Dollard, and Biswas (2006) and Chakrabarti (2004), have assessed many issues, for instance, the role of SHG federations in providing sustainability of SHGs, the economic and personal empowerment of women and the role of microfinance in poverty eradication.…”
Section: Introductionmentioning
confidence: 99%
“…Moyle, Dollard and Biswas (2006) and EDA Rural System and APMAS, (2006) discussed mainly various socio-economic parameters of SHG members related to the situation during pre-SHG and post-SHG periods. Further, Khandker (2005) applying panel methods (using a 1999 resurvey) concludes that microcredit benefits the 'very poor' even more than the 'moderately poor'.…”
Section: Section-ii Impacts Of Microfinance: Conceptual Frameworkmentioning
confidence: 99%